Analisis Faktor - Faktor Yang Mepengaruhi Kinerja Pengguna Sistem Informasi Akuntansi Pada Bank Konvensional(StudiEmpiris di KabupatenWonogiri) - Mukholid, Wildanu; , Dr. Erma Setiawati, Ak, MM (2016)
Intention of this research is to analyse and test influence of top management support, involvement of consumer of accountancy information system, system development formalization, and ability of technique of personal have an effect on to accountancy information system at conventional bankin Sub-province of Wonogiri. This research use quantitative method by using obtained primary data of questioner. Population in this research is entire public bank employees in Sub-province region of Wongiri. Sampel in this research is employees using accountancy information system computerized and ready to be made by responder. Method gathering of sampel use technique of purposive random sampling. used analyzer cover validity test and test of reliabilities, test of normality, test of multikolinierities, test of heteroskedastisities, test of doubled linear regression, test of F, coefficient test of determinasi R2, and test of t. Pursuant to result of data analysis can be concluded that top management support variable have an effect on to accountancy information system, because tcount (2,327) > ttable (2,028) with the level of significant equal to 0,026 < (0,05). While variable involvement of consumer of accountancy information system have an effect on to accountancy information system, because tcount (3,296) > ttable (2,028) with the level of significantequal to 0,002 < (0,05). Hereinafter variable of formalisasi system development have an effect on to accountancy information system, because tcount (4,974) > ttable (2,028) with value of significantequal to 0,000 < (0,05). Then at variable ability of technique of personal have an effect on to accountancy information system, because tcount (4,105) > ttable (2,028) with the level of significantequal to 0,000 < ( 0,05). Result of test of F obtained by value of Fcount (11,845) >Ftable (2,63) with its value it equal to 0,000 at the level of significant0,05 hence can be concluded that as a whole independent variables have an effect on by simultan to accountancy information system. Adjusted R2 equal to its 0,520 meaning of top management support, involvement of consumer of accountancy information system, system development formalization, and ability of technique of personal can explain accountancy information system variabilitas equal to 52%. Keyword:Top Management Support, Involvement of Consumer of Accountancy Information System, System Development Formalization, Ability of Technique of Personal andAccountancy Information System